Bank affiliation and timing ability of mutual funds: Evidence from China - Wang, Xiaoxiao; Zhang, Xueyong (Journal of Banking & Finance, 2024)
This study analyzes the impact of commercial bank affiliation on mutual funds' timing ability. In contrast to the findings for developed markets, affiliated funds outperform unaffiliated funds in China. Here, we explain affiliated funds' outperformance using 3,351 Chinese equity and hybrid mutual funds between 2008 and 2019 to demonstrate that affiliated funds are better timed than unaffiliated funds. One underlying mechanism is that affiliated funds benefit from information advantages due to the unique position of commercial banks in China's economy. Further findings reveal that better timing ability subsequently benefits commercial banking groups, indicating that commercial banks and affiliated funds share a mutual incentive compatibility relationship. A quasi-natural experiment of variations in bank affiliation verifies a causal interpretation of these findings, and our results continue to hold across a set of robustness tests.